2013
DOI: 10.1073/pnas.1208302110
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the role of cladogenesis in macroevolution by integrating fossil and molecular evidence

Abstract: Assessing the extent to which population subdivision during cladogenesis is necessary for long-term phenotypic evolution is of fundamental importance in a broad range of biological disciplines. Differentiating cladogenesis from anagenesis, defined as evolution within a species, has generally been hampered by dating precision, insufficient fossil data, and difficulties in establishing a direct link between morphological changes detectable in the fossil record and biological species. Here we quantify the relativ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
30
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 39 publications
(33 citation statements)
references
References 62 publications
(75 reference statements)
3
30
0
Order By: Relevance
“…(Well, maybe.) Although this model is not the only one that might account for a correlation between divergence and speciation (Rabosky 2012), the evidence mentioned earlier (e.g., Mattila and Bokma 2008;Venditti and Pagel 2010;Strotz and Allen 2013) is consistent with it. So is evidence suggesting a break between intraspecific evolution and divergence between reproductively isolated populations.…”
Section: Reconciling Punctuated Equilibria With Population Geneticssupporting
confidence: 61%
See 1 more Smart Citation
“…(Well, maybe.) Although this model is not the only one that might account for a correlation between divergence and speciation (Rabosky 2012), the evidence mentioned earlier (e.g., Mattila and Bokma 2008;Venditti and Pagel 2010;Strotz and Allen 2013) is consistent with it. So is evidence suggesting a break between intraspecific evolution and divergence between reproductively isolated populations.…”
Section: Reconciling Punctuated Equilibria With Population Geneticssupporting
confidence: 61%
“…Although punctuated gradualism has been claimed for some lineages of planktonic Foraminifera, which provide exceptionally complete fossil records (e.g., Malmgren et al 1983), Gould and Eldredge (1993) claimed that many studies find temporal overlap, supporting their model. A recent comprehensive analysis of 337 Cenozoic "speciation" events in Foraminifera concluded that at most 19 % of Cenozoic events (last 65 million years) and 10 % of Neogene events (last 23 million years) represented change within nondividing lineages: The great majority revealed temporal overlap, and hence biological speciation (Strotz and Allen 2013). Analyses of living species can also shed light on the question.…”
Section: Punctuated Equilibriamentioning
confidence: 98%
“…The combination of fossil and molecular data has the potential to form a powerful toolkit with which to tackle longstanding macroevolutionary issues (Strotz and Allen 2013;Garwood et al 2014;Longrich et al 2015). Fossils represent a unique information resource that can be invaluable for informing on patterns of biogeography, recognizing patterns of character acquisition, and inferring the timing of divergences.…”
Section: Discussionmentioning
confidence: 99%
“…For paleontologists, the best evidence for anagenesis requires dense stratigraphic sampling and precise radiometric dating, temporally successive specimens of close phylogenetic relationship, clear stratigraphic data for specimens, and a high sample size that includes growth series11819202425. Tyrannosaurs represent one of the few dinosaur clades that meet these criteria7262728.…”
mentioning
confidence: 99%